2020
DOI: 10.1017/s0029665120001871
|View full text |Cite
|
Sign up to set email alerts
|

Oral preload of calcium reduces food intake via enhanced PYY secretion in rats

Abstract: AbstractIntroductionDietary calcium has been proposed to reduce appetite (or to enhance satiety) in human studies. However, underlying mechanisms are still unclear. In animal and cell studies, it has been demonstrated that activation of the calcium-sensing receptor induced secretion of anorexic gut hormones such as cholecystokinin (CCK) and glucagon-like peptide-1 (GLP-1) from enteroendocrine cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For instance, Hira et al found that an oral preload of calcium could reduce food intake in rats through increasing PYY secretion. [6] However, excessive calcium intake increased the risk of cardiovascular events, urolithiasis, and even fractures, [27] which may be the harm of promoting PYY secretion by supplementing excessive calcium instead of LCK11. According to the results of the colonization of LCK11 in the intestine and its effect on PYY expression in different parts of the intestine, LCK11 colonized and promoted the transcription and translation of PYY most significantly in the rectum, which implied that the ability of LCK11 to promote PYY secretion might be associated with the number of LCK11 local colonization.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Hira et al found that an oral preload of calcium could reduce food intake in rats through increasing PYY secretion. [6] However, excessive calcium intake increased the risk of cardiovascular events, urolithiasis, and even fractures, [27] which may be the harm of promoting PYY secretion by supplementing excessive calcium instead of LCK11. According to the results of the colonization of LCK11 in the intestine and its effect on PYY expression in different parts of the intestine, LCK11 colonized and promoted the transcription and translation of PYY most significantly in the rectum, which implied that the ability of LCK11 to promote PYY secretion might be associated with the number of LCK11 local colonization.…”
Section: Discussionmentioning
confidence: 99%